Inter-Municipal Cooperation: Challenges in Europe and in Slovenia - Iztok RAKAR; Bojan TIČAR; Maja KLUN (Transylvanian Review of Administrative Sciences, 2015)
The f nancial crisis has once again brought up the question of the ‘perfect size’ of local gov-ernments and revealed a new dimension of the eternal question of f nancing self-governing local communities. The paper presents a comparative overview of efforts to determine the ‘perfect size’ of municipalities and recent reforms in different countries aimed at enabling municipalities to ensure both local-level democracy and identity, and economic eff ciency in the delivery of pub-lic services. One of the most popular ways for achieving this goal is to promote various forms of inter-municipal cooperation. Some forms of inter-municipal cooperation already exist in Slovenia; a considerable break-through in this regard occurred in 2007, but such an approach would have been possible much earlier. Analyses show that this change is due to changes in the rules regarding co-f nancing. Despite the fact that neither literature nor politics in Slovenia sees inter-municipal cooperation as an alternative to merging municipalities, experi-ences show that practice will proceed in this di-rection.